Answer:
63.y = -4 and x = 2
64. x = 3 and y = 5
Explanation:
63.
We are given that
y = x - 6
x + y = -2
We need to use the substitution method, so let's find x in terms of y.
Adding 6 to both sides of the first equation, we get
x = 6 + y
Substituting 6 + y into the second equation, we get
(6 + y) + y = -2
2y + 6 = -2
2y = -8
y = -4
Now, solving for x, we get
x + (-4) = -2
x = 2
Checking our answer by substituting these into the first equation,
-4 = 2 - 6?
-4 = -4
So that's all good
64.
x + y = 8
-x + 2y = 7
Adding the two equations together will eliminate the x variable, allowing us to solve for y. This is the addition/elimination method
3y = 15
y = 5
Putting y back into the first equation gives us
x + 5 = 8
x = 3
Checking our answer in the second equation, we get
-(3) + 2 (5) = 7?
-3 + 10 = 7?
7 = 7 :)